Ajustamento intercultural de executivos japoneses expatriados no Brasil - Kubo, Edson Keyso de Miranda (2011)
International assignments of executives continues to be essential for the internationalization of the enterprises, control of subsidiaries, knowledge transference, international business and it seems that the number of expatriates in the world shows no signs of slowing down. The international literature on expatriation has shown the intercultural adjustment as the determinant factor of the expatriate’s success in his/her international assignment. The model of international adjustment from Black et al. (1991) is the reference for empirical research and practical recommendations involving policies of international human resource management. According to this model without intercultural adjustment, the expatriate will not be effective and will fail in his/her international assignment. The intercultural adjustment is a multidimensional construct that have been depicted in many ways, but it also has been little explored and not sufficiently explained. Under this context, the Japanese expatriates are taken as examples of success in international assignment due to their lowest failure rates in the world (TUNGLI; PEIPERL, 2009). However, the research's results show that intercultural adjustment does not seen to be relevant to the their success in international assignments, which contradicts the literature on this theme. In this thesis the author carried out a methodological approach based on exploratory and qualitative research and observed that the process of Japanese expats' intercultural adjustment does not follow the Black et al.(1991a) model’s recommendations and logic. Three groups of expatriates (Bulletproof, Adventurer, Conformist) were also identified so that it allowed a profound analysis of the organizational and individual factors that facilitate and also difficult their intercultural adjustment.